Nuclear transcription factor kB (NF-kB) activity in lymphocyte populations in children with Wilson-Konovalov disease - O. V. Kurbatova; S. V. Petrichuk; D. G. Kuptsova; G. B. Movsisyan; T. V. Radygina; A. D. Komarova; A. O. Anushenko; E. V. Freidlin; E. L. Semikina; A. S. Potapov; A. P. Fisenko (Медицинская иммунология, 2023)
Wilson's disease (WD) is a rare hereditary disease caused by a deficiency of the ATF7B transporter. The accumulation of copper can cause damage to organs and cells, mainly the liver. Copper exposure can modulate cytokine synthesis through molecular and cellular signaling pathways, including the nuclear transcription factor NF-kB pathway. NF-kB is the main regulator of inflammation and cell death, acts as a central link between liver damage, fibrosis and hepatocellular carcinoma. An excess of NF-kB-dependent cytokine response stimulates inflammatory reactions, but excessive inhibition of NF-kB can negatively affect the viability of hepatocytes. Method of flow cytometry with visualization — Amnis ImageStreamX allows to evaluate the activity of NF-kB (% of activated cells in cell populations). The aim: to evaluate the activity of NF-kB in lymphocyte populations in children with WD disease. Immunophenotyping of lymphocytes and assessment of the level of translocation of NF-kB were performed in 52 children with WD and in 25 children of comparison group. The mass concentration of copper in daily urine was determined by atomic absorption method using the AAnalyst 800 spectrometer. In children with WD, the content of cells with NF-kB translocation varied from 5 to 90% depending on the lymphocyte population; the highest level was detected in B cells — 57.5 (37-68) %. A significant difference in distributions of the number of cells with NF-kB translocation between WD and healthy children was shown (F-criterion, p < 0.01). In most cases, children with WD are characterized by a decrease in the activity of NF-kB in populations of B cells (in 43% of cases), T helper cells (48%), T cytotoxic (44%) and Th17 lymphocytes (41%). In children with WD, the concentration of copper varied from 9.7 to 2582 mcg/day, Me = 616 (210-1173). A direct relationship was obtained between the copper content in urine and the level of translocation of NF-kB in B lymphocytes, r = 0.34, p = 0.016. The activity of the NF-kB correlates with biochemical markers of the severity of liver damage (ALT, AST, GGT) and with copper content in urine. The study of the NF-kB signaling pathway seems promising for a better understanding of the pathogenetic mechanisms of the formation of inflammation and liver fibrosis in children with WD.